Answer:
10cos(5x)sin(10x) = 5[sin (15x) + sin (5x)]
Step-by-step explanation:
In this question, we are tasked with writing the product as a sum.
To do this, we shall be using the sum to product formula below;
cosαsinβ = 1/2[ sin(α + β) - sin(α - β)]
From the question, we can say α= 5x and β= 10x
Plugging these values into the equation, we have
10cos(5x)sin(10x) = (10) × 1/2[sin (5x + 10x) - sin(5x - 10x)]
= 5[sin (15x) - sin (-5x)]
We apply odd identity i.e sin(-x) = -sinx
Thus applying same to sin(-5x)
sin(-5x) = -sin(5x)
Thus;
5[sin (15x) - sin (-5x)] = 5[sin (15x) -(-sin(5x))]
= 5[sin (15x) + sin (5x)]
Hence, 10cos(5x)sin(10x) = 5[sin (15x) + sin (5x)]
A. 5
5*6=30, so 5/30= 1/6th
Answer:
see explanation
Step-by-step explanation:
The Remainder theorem states that if f(x) is divided by (x - h) then
f(h) is the remainder, thus
division by (x - 1) then h = 1
f(1) = 4(1)³ - 7(1)² - 2(1) + 6
= 4 - 7 - 2 + 6 = 1 ← remainder
The factor theorem states that if (x - h) is a factor of f(x), then f(h) = 0
Here f(1) = 1
Hence (x - 1) is not a factor of f(x)
Answer:
Triangle A and B
Step-by-step explanation:
The lengths from triangle A is being doubled to make the lengths of triangle B. They also have the same angles.